(untitled) (Global Journal of Science Frontier Research, 2023)
Why do photons exist Classical physics gives a derivation but can not explain the essence and strange properties of photons Quantum theory suggests that photons are nonlocal particle and differ significantly from ordinary microscopic particles However no theory can provide a concrete image of the photon which causes difficulties in the definition of a single photon Photons can be obtained from light pulses the number of which follows the Poisson distribution and can also be defined from the light power the photons is actually a kind of weakest light source